Fifth Five Year Plan Draft Annual Plan 1975-76 Volume II (Statements) Government of Bihar - Planning Commission (Planning Commission, 1974)
Agriculture Education and Research Crop Husbandry Land Reforms Minor Irrigation Soil Conservation Ayacut Animal Husbandry Dairy and Milk Supply Forests Fisheries Agriculture Marketing and Storage.
Planning Department Government of Bihar